(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The human lung's intricate branching patterns present a captivating yet complex system, challenging traditional anatomical analysis. In this abstract, we introduce the concept of fractal dimensions, specifically focusing on the box counting method, as a mathematical tool to navigate the intricacies within the pulmonary landscape.The branching patterns within the human lung are inherently dynamic, resembling a tree-like structure that extends from the trachea to the finest airways. Traditional metrics prove insufficient in capturing the richness of these patterns, leading us to explore the application of fractal dimensions.Fractal dimensions, with their capacity to quantify irregularities and self-similarities, emerge as a crucial bridge between biology and mathematics. This abstract serves to underscore the significance of employing fractal dimensions to comprehend the irregular and self-repeating nature of biological structures, particularly the intricate branching architecture of the lungs.As we delve into the intersection of biology and mathematics, this abstract invites readers to consider fractal dimensions as a means of unraveling hidden orders within the apparent chaos of lung branching structures. Our subsequent focus on the box counting method promises a deeper understanding of the complexities embedded in the respiratory symphony. This abstract serves as an entry point into decoding the language intricately written within the delicate branches of the human lung.